Cross-Reactivity Between Influenza Matrix- and HIV-1 P17-Specific CTL-A Large Cohort Study - Hueckelhoven, Angela; Etschel, Jennifer; Bergmann, Silke; Zitzelsberger, Kathrin; Müller-Schmucker, Sandra; Harrer, Ellen G.; Harrer, Thomas (Jaids-Journal of Acquired Immune Deficiency Syndromes, 2015)
It has been reported that HIV-1-specific cytotoxic T cells (CTL) recognizing the HLA-A2-restricted p17 epitope SLYNTVATL (SL9) can cross-react with the HLA-A2-restricted influenza matrix epitope GILGFVFTL (GL9). So far, the prevalence of GL9-cross-reacting HIV-1-specific CTL in larger cohorts of HIV-1-infected patients is unknown, and there are no data yet on whether SL9/GL9-cross-reactive CTL may influence the course of HIV-1 infection.We analyzed the presence of SL9/GL9-cross-reacting CTL in a cohort of 175 HLA-A2-positive HIV-1-infected patients. Peripheral blood mononuclear cells were stimulated in vitro with SL9 and GL9 peptides, and outgrowing cell lines regarding cross-reactivity and recognition of viral variants in ?-interferon enzyme-linked immunospot assays were analyzed.SL9- and GL9-specific CTL could be generated in 52.6% and 53.7% of 175 patients, respectively. Both SL9- and GL9-specific CTL were more frequently observed in patients on antiretroviral therapy (ART). Of the 92 SL9-specific CTL and the 94 GL9-specific CTL, 65.2% and 66%, respectively, showed at least partial SL9/GL9 cross-reactivity. SL9/GL9-cross-reactive CTL could be detected in 42.9% of the 175 patients. Recognition of SL9 was associated with lower viral loads and higher CD4 cell counts in patients on ART. Patients with GL9/SL9 cross-reactivity displayed similar CD4 cell counts than patients without GL9/SL9-cross-reactive cells. GL9/SL9-cross-reactive cells were associated with higher viral loads in patients on ART.Partially SL9/GL9-cross-reactive CTL are frequently observed in HIV-1-infected patients. So far, we could not detect a significant influence of the presence of SL9/GL9-cross-reacting CTL on the course of HIV-1 infection.
EVALuna2:13143